Simultaneous heterogeneous photo-Fenton degradation of azithromycin and clarithromycin in wastewater treatment plant effluent - Guardiano, Matheus Gabriel [UNESP]; Carena, Luca; Pazzi, Marco; Vione, Davide; Nogueira, Raquel Fernandes Pupo [UNESP] (Elsevier, 2025)
This study aimed to investigate the degradation of the macrolide antibiotics azithromycin (AZT) and clarithromycin (CLA) in wastewater treatment plant (WWTP) effluent, applying a heterogeneous photo-Fenton process with a copper-modified iron oxide (prepared by coprecipitation) as a model catalyst. The effects of solution pH and initial H2O2 concentration on the simultaneous degradation of the macrolides were studied, and the heterogeneous photo-Fenton degradation kinetics of the macrolides was compared to that of a sulfonamide antibiotic (sulfamethoxazole, SMX). Experiments using tert-butanol as a hydroxyl radical scavenger demonstrated the key role of HO[rad] in macrolide degradation, whereas a minor contribution to SMX degradation was observed. SMX degradation was inhibited in WWTP effluent compared to ultra-pure water. By contrast, macrolide degradation was not affected by this matrix, highlighting the different degradation mechanisms involved in the two antibiotic classes. The initial transformation products of AZT were identified using a HPLC-MS/MS system, which demonstrated the hydroxylation of the macrolide ring as the main degradation pathway. These findings enhanced our understanding of the degradation mechanisms of macrolides and the reactivity of these little explored antibiotics in the heterogeneous photo-Fenton process.
Keywords: Copper-modified magnetite; Heterogeneous photo-Fenton process; Macrolides; Sulfamethoxazole